Peningkatan Kepekaan Gender Dalam Jurnalisme - Yusuf, Iwan Awaluddin (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Mass media and jurnalism in Indonesia has been insensitive the notion of gender equality. Such insensitivity is apparent given: (1) the way journalists present fact, (2) the posision of media, (3) the position of journalist, and journalistic product. In order to improve the sensitivity, this article outlines what to be done ang how to do it.